The preferred CSL misorientation distribution in polycrystalline SrTiO3. - Park, M; Shih, S; Cockayne, D (2007)
Electron backscattered diffraction is used to investigate the preferred CSL (coincidence site lattice) distribution of polycrystalline SrTiO(3) as a function of annealing times (1 h and 16 h). Comparison of the CSL misorientations suggests that the CSL boundary energy plays a role in the preferred grain growth.